Modelling the effect of CO2 loading of aqueous potassium glycinate on CO2 absorption in a membrane contactor - Nieminen, Harri; Maksimov, Pavel; Laari, Arto; Koiranen, Tuomas (Frontiers in Chemical Engineering, 2022)
CO2 absorption into aqueous potassium glycinate in a polypropylene membrane contactor was modelled using two alternative models: a 1D model and a 1D-2D model considering axial diffusion in the liquid phase. Models were fitted to experimental data using various fitting parameters, which were compared. Experiments were carried out under industrially relevant conditions characterized by CO2-loaded absorbent entering the contactor and high degree of reactant conversion over the contactor. The experiments and models were developed to specifically investigate the effect of changes in solution CO2 loading at contactor inlet. This is a key issue rarely reported in the literature, especially for amino acid salt solutions. Unexpectedly, the 1D model was found to explain the experimental results more accurately compared to the more complex 1D-2D model. This was the case for the base models, using only the membrane mass transfer coefficient as a fitting parameter, and the final models introducing secondary fitting parameters. The 1D model was found to show the best experimental fit following fitting of the equilibrium constant used in prediction of the enhancement factor. The 1D-2D model showed the best fit following correction of potassium glycinate diffusivity as a function of solution CO2 loading. The 1D approach was found to result in a computationally effective model with good fit to the present experimental data. This model provides a good basis for further development and could be considered for use in contactor design and optimization studies. It is suggested that various model simplifications led to inability of the 1D-2D model to accurately predict the experimental results.